A case study of the National Hockey League : the question of expansion - Cintron, Alicia; Levine, Jeffrey F.; Hambrick, Marion E. (London : Human Kinetics, Inc., 2016)
At the upcoming National Hockey League (NHL) owners' meeting in Boca Raton, Florida, team owners are meeting to discuss franchise expansion. League executives believe adding two new franchises would increase viewership and popularity, generate higher revenues, and balance the Eastern and Western Conferences. However, it is unclear whether viable markets for two new franchises exist. Despite this concern, five ownership groups representing five distinct North American cities--Seattle, Washington; Las Vegas, Nevada; Kansas City, Missouri; Indianapolis, Indiana; and Qu?bec City, Qu?bec, Canada--have emerged as viable candidates for an expansion franchise. Given the five ownership groups, the NHL now needs to decide which cities to choose as the new homes for its two expansion teams, based on each city's viability to host a professional team. Each ownership group will present a case on why its city should be the future home of a new NHL expansion team.
Originally published in Cintron, A., Levine, J. F., & Hambrick, M. E. (2016). National Hockey League: The question of expansion. Case Studies in Sport Management, 5(1), 17-23. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; National Hockey League; Hockey teams -- United States; Hockey teams -- Canada